Certification training of social workers and social managers: the experience of Ukrainian Catholic University - Slozanska, Hanna; Stelmakh, Svitlana; Krynytska, Iryna (Social work and education, 2022)
The article defines the need and relevance of creating different training programs for social workers and social managers in the post-graduate system taking into consideration the development of a new system of social work and rapid social transformations in Ukraine. The authors emphasize the need to develop new approaches to providing “long life education”, such as short-term educational programs. The last should correspond to the "Global Standards for Social Work Education and Training" and the competency-based approach to learning. The paper presents the certificate program "Social work: the path to professionalism", developed by the professors of the Pedagogy and Social Work Department of Ukrainian Catholic University in response to numerous requests from employers. The structure of the program is highlighted: it has three levels - basic, professional and managerial; each of which contains several training modules. Its content is characterized. The algorithm of the implementation of the Certificate program in the process of improving the qualifications of social workers and managers of social service providers in the territorial communities of Rivne, Volyn, Khmelnytskyi and Chernivtsi regions is described. The procedure for selecting learners and the organization of the educational process due to the program has been characterized. The results of the evaluation of the effectiveness of the Certificate program "Social work: the path to professionalism", which was implemented by the "Ukrainian Catholic University" in the process of improving the qualifications of social workers and social managers of communal and public sector institutions that provide social services in territorial communities, are presented. It has been proven that a competent approach to educational process, taking into account the professional needs of potential learners, a hybrid, flexible format and personalization of training, the use of various forms and methods while presenting educational material, an inextricable connection between theoretical concepts and practice, as well as reinforcement by the speakers’ own professional experience, gives a good result in improving the qualifications of those who are already in the profession and wish to be better in it. The results of evaluating of the effectiveness of the developed program among the participants involved in the training proved the success of its implementation in the proposed format.